2006
DOI: 10.1128/aem.72.3.2235-2238.2006
|View full text |Cite
|
Sign up to set email alerts
|

Selective Biodegradation of S and N Heterocycles by a Recombinant Rhodococcus erythropolis Strain Containing Carbazole Dioxygenase

Abstract: The carbazole dioxygenase genes were introduced into a dibenzothiophene degrader. The recombinant Rhodococcus erythropolis SN8 was capable of efficiently degrading dibenzothiophene and carbazole simultaneously. SN8 could also degrade various alkylated derivatives of carbazole and dibenzothiophene in FS4800 crude oil by just a one-step bioprocess.Acid precipitation resulting from fossil fuel combustion has driven enormous efforts to remove contaminants from fossil fuels. Heteroatoms such as nitrogen and sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…1). The DBT transformation rate was equivalent to that of the host strain R. erythropolis XP and the previously described recombinant strain SN8 containing carbazole dioxygenase (38). These results also indicated that the introduced CA-degrading enzymes had no significant effect on the DBT biotransformation rate.…”
supporting
confidence: 58%
“…1). The DBT transformation rate was equivalent to that of the host strain R. erythropolis XP and the previously described recombinant strain SN8 containing carbazole dioxygenase (38). These results also indicated that the introduced CA-degrading enzymes had no significant effect on the DBT biotransformation rate.…”
supporting
confidence: 58%
“…strain HR199 and CarAa from Pseudomonas sp. strain XLDN4-9 (37,38). Other research also showed that ␣ subunit alone can control substrate specificity in dioxygenases of the naphthalene family (39,40) and toluene/biphenyl family (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, biocatalytic processes were cheaper, operated under milder conditions, and had higher selectivity. There have been numerous efforts to develop a biotechnological process for biodesulfurization of fossil fuels using specific isolated strains (Yu et al, 2006b;Yu et al, 2006c). A small number of mesophilic genera, Arthrobacter, Bacillus, Corynebacterium, and Rhodococcus, are known to be able to remove sulfur from dibenzothiophene (DBT), the model sulfur compound in petroleum, via a sulfur-specific manner without affecting the carbon skeleton thus the calorific value of the fuel value remains preserved (Xu et al, 2006).…”
mentioning
confidence: 99%